Legal Education and Human Rights in a Global Age - Anumba, Florence N. (Mediterranean Journal of Social Sciences, 2012)
The development of the concept of justice is connected with the development of theories of law, jurisprudence andpolitics. But, in the beginning was the philosophy of the existence of man, the philosophy was the survival of the fittest. Then,no other right seemed to belong to man except that of the defence of his life. The Greek period and the emergence of civilsociety paved way for legal era. Various instruments of history brought nations under one umbrella, hence myriad of worldconferences on education have followed since the 50s, such that education has in the contemporary times become the mostcrucial asset of every society. On its part, the Universal Declaration of Human Rights of 1948 stipulated the right of everycitizen of the world to education. A day like this, in 1990, a world conference on Education For All (EFA) was held in Jomtiem,Thailand. Contemporary societies acknowledge education as the key to acquiring the desired potentials necessary for individualwell-being and national development. Legal education mould character and serves as a veritable tool for social regulation. Thispaper dwells on the education based on law which encompasses the rights of citizens protected by law.